Community Empowerment Through Bamboo Laminate Technology as Part of Disaster Conservation and Mitigation in Wonokerto, Turi, Sleman, Yogyakarta - Krisdiyanto, Didik; Farihah, Tutik; Supriyati, Hikmah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Bamboo is included in the classification of grasses, but because of its large size compared to other types of grass, bamboo is also called "giant grass". Bamboo has the ability to grow fast, reaching 30-100 cm per day. The target of this community service is the empowerment of the Daerah Istimewa Yogyakarta (DIY) Search and Rescue (SAR) Team in Wonokerto to become a transfer agent for laminated bamboo technology through the training provided. The approach used in this community service is based on research that has been carried out in universities (research-based community development) by involving potential communities as social agents and potential assets (assessed-based community development) in the community to support Mount Merapi as a National Strategic Area (KSN). In training implementation, the participants showed high contribution in providing training material, attendance, and involvement. Based on the training survey on bamboo laminate technology, 80.59% of respondents know the identification material, stage of preparation material, identification of connection mixture, identification of lamination stage, and quality check of laminated bamboo lumbar. The proposed training or assistance for sustainability community services are marketing, business planning, product design, and quality products.